High refractive index nanoimprint lithography resin

JP2025505955APending Publication Date: 2025-03-05ADDISON CLEAR WAVE COATINGS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024544673
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-25
Filing Date
2023-01-24
Publication Date
2025-03-05

Smart Images

  • Figure 2025505955000014
    Figure 2025505955000014
  • Figure 2025505955000001
    Figure 2025505955000001
  • Figure 2025505955000002
    Figure 2025505955000002
Patent Text Reader

Abstract

A photo-nanoimprint lithography (P-NIL) resin is disclosed, the P-NIL resin comprising a crosslinkable organic binder; solvent-based inorganic nanoparticles dispersed in the P-NIL resin; and a solvent configured to evaporate; the P-NIL resin has a viscosity in the range of 4,000 to 6,000 centipoise at 25° C. after evaporation of the solvent prior to curing the P-NIL resin; and the P-NIL resin has a refractive index greater than 1.6 at 589 nm and a glass transition temperature greater than 50° C. after curing with a photoinitiator.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is a nonprovisional patent application claiming priority under 35 U.S.C. § 119(e) to U.S. Provisional Patent Application Serial No. 63 / 302,656, filed January 25, 2021.

[0002] The present invention relates to photocurable compositions for nanoimprint lithography (NIL) processes, and more particularly to resins for use in patterning nanometer-scale structures. [Background technology]

[0003] Nanoimprint lithography (NIL) is a technique for fabricating nanometer-sized features in materials. In one version of NIL, a curable resin, the imprint resin, is applied to a pattern or mold and cured either by heat or photolysis, which initiates polymerization of the resin. The imprinted material is then removed from the mold, and the mold may be reused. In general, NIL approaches promise low-cost, short cycle times, and high-yield manufacturing processes for sub-micrometer components of small devices.

[0004] When the imprint resin for the NIL process is cured by photolysis, the technique is called photo-nanoimprint lithography (P-NIL) or UV-nanoimprint lithography (UV-NIL). The term 2P (for photopolymers) refers to similar techniques used on the micrometer or nanometer scale.

[0005] Photo-nanoimprint lithography (P-NIL) or UV-nanoimprint lithography (UV-NIL) is a cost-effective process used for the mass production of optical, optoelectronic, or electronic components containing nanometer-sized features. Photopolymer (2P) resins are photosensitive, typically organic materials that can be used in the P-NIL process to form patterned films on substrates.

[0006] In a typical P-NIL process, a resin may be coated onto a substrate such as glass or silicon. The resin may contain a solvent. Solvent removal is then required and may be accomplished by heating the resin on the substrate. A stamp or master template containing nanometer-sized features is pressed onto the resin. The resin is then cured via photolysis using ultraviolet (UV) or visible light. The stamp is then removed to produce the embossed product. High tensile strength and stiffness are important mechanical properties for P-NIL or 2P resins. Lack of shrinkage during the curing process and in the cured state are also important properties for P-NIL / 2P resins.

[0007] Since P-NIL technology can be achieved at room temperature, the P-NIL process is simpler than conventional hot embossing and injection molding techniques. The P-NIL method is particularly attractive for mass production of devices with nanometer (submicron) scale features, since the cycle time can be very short, e.g., the top or second information layer of a Blu-ray disc is produced by P-NIL with a cycle time of only a few seconds. The fast, accurate, and direct patterning and repeatable replication in a single step of complex nanometer scale patterns makes this technique compelling compared to expensive techniques such as e-beam or helium ion beam lithography. The versatility of the technique enables the fabrication of unique nanoscale devices by P-NIL for a variety of applications including optics, plasmonics, and even biotechnology. Recent advances in the throughput and yield of the P-NIL process demonstrate its potential for adoption in mainstream semiconductor device fabrication.

[0008] Applications of P-NIL are wide-ranging, spanning flexible displays, wearable electronics, facial recognition, artificial intelligence, biomedicine, and semiconductor chips. Notable applications of P-NIL include the fabrication of optical devices for augmented, virtual, and mixed reality (AR / VR / MR), optical sensors for autonomous vehicle applications, and biosensors. The P-NIL method can also be used to fabricate photonics and optics applications, such as diffractive optical elements (DOEs), which contain optical diffusers and waveguides that control the phase of transmitted light.

[0009] For optical applications, high refractive index (RI) materials are desirable because they can provide thin lenses and increase the field of view (FOV) of devices. In optics, the refractive index of a material describes how fast light passes through the material, and the RI of a lens determines how light is bent as it passes through the lens. Today, glasses exist with refractive indices ranging up to 2.0 at 589 nm. However, if features are required on the surface of the glass, etching patterns into the glass is expensive and time consuming. An alternative to etching into glass is to create surface features on a thin layer of polymeric material by NIL processes. Importantly, the cured resins used in these NIL processes must have a refractive index matched to the glass to reduce internal reflections; if the refractive indices are perfectly matched, there is no internal reflection or refraction of light through the glass-film interface.

[0010] Traditional P-NIL resins are organic prepolymer formulations that typically have a cured RI in the range of 1.45-1.55 at 589 nm. Increasing the RI of P-NIL resin materials enables device miniaturization, which is important for augmented, virtual, and mixed reality (AR / VR / MR) applications.

[0011] There have been attempts to increase the RI of the cured resin to more than 1.6. For example, U.S. Patent Application No. 2022 / 0334475 discloses a photocurable composition containing metal oxide nanoparticles, a component (R) that is an unsaturated acid metal salt, a photopolymerizable compound other than the compound corresponding to component (R), and a photoradical polymerization initiator. As described above, the prior art does not provide a resin composition having a RI of more than 1.6 at 589 nm and a viscosity in the range of 4,000 to 6,000 centipoise. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] U.S. Patent Application No. 2022 / 0334475 Summary of the Invention [Problem to be solved by the invention]

[0013] Therefore, it is desirable to utilize a P-NIL resin having an RI in the range of 1.6 to 2.0 at 589 nm and a viscosity in the range of 4,000 to 6,000 centipoise at 25°C. [Means for solving the problem]

[0014] In one embodiment of the present disclosure, a photo-nanoimprint lithography (P-NIL) resin is disclosed. The P-NIL resin includes a crosslinkable organic binder; solvent-based inorganic nanoparticles dispersed in the P-NIL resin; and a solvent configured to evaporate; the P-NIL resin has a viscosity in the range of 4,000 to 6,000 centipoise at 25° C. after evaporation of the solvent prior to curing the P-NIL resin; the P-NIL resin has a refractive index greater than 1.6 at 589 nm and a glass transition temperature greater than 50° C. after curing with a photoinitiator.

[0015] In another embodiment of the present disclosure, a photopolymer (2P) resin is disclosed for use in photonic nanoimprint lithography for photonics and optical applications. The 2P resin comprises an organic compound and inorganic nanoparticles with a size of less than 30 nanometers; the organic compound has a minimum refractive index value of 1.5 and is selected from the group consisting of acrylate-based resins, epoxy-based resins, materials containing brominated aromatic compounds, and sulfur-containing compounds; the inorganic nanoparticles have a minimum refractive index value of 1.6 at 589 nm and are selected from the group consisting of silicon carbide, silicon nitride, zinc oxide, zirconium oxide, and titanium oxide; the organic compound and the inorganic nanoparticles are combined in a prepolymerized liquid medium; the cured product obtained after the curing process has a refractive index of 1.65 or more at 589 nm and a glass transition temperature of 40° C. or more.

[0016] In another embodiment of the present disclosure, a method for making a photo-nanoimprint lithography (P-NIL) resin is disclosed, the method comprising the steps of: providing an uncured P-NIL resin comprising a crosslinkable organic binder, solvent-based inorganic nanoparticles dispersed in the uncured P-NIL resin, and a solvent having a viscosity in the range of 4,000-6,000 centipoise at 25° C.; coating the uncured P-NIL resin on a substrate; applying heat to the uncured P-NIL resin to evaporate the solvent; impressing the uncured P-NIL resin with a stamp having nanometer-sized features; curing the uncured P-NIL resin with a photoinitiator; and removing the stamp, the resulting P-NIL resin having a refractive index greater than 1.6 at 589 nm, a glass transition temperature greater than 50° C., and nanometer-sized features. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a flow chart of steps in a photo-nanoimprint lithography process using the 2P resin of the present disclosure, according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Referring now to the figures, and in particular to the depicted P-NIL process shown in FIG. 1, disclosed herein is a photo-nanoimprint lithography (P-NIL) resin 100 having high refractive index and high mechanical performance for use in photo-nanoimprint lithography (P-NIL) or UV-nanoimprint lithography, as well as a method of formulating the P-NIL resin 100 for P-NIL applications. The P-NIL resin 100 can be a high refractive index organic / inorganic resin used in P-NIL applications. The P-NIL resin 100 can have a substantially higher RI than conventional organic resins and exhibit acceptable mechanical or toughness performance properties. The P-NIL resin 100 can be formulated for use in photonics and optical applications such as optical diffusers and waveguides, as well as AR / VR / MR devices. The P-NIL resin 100 may be referred to as a "2P resin" as is commonly known by those skilled in the art.

[0019] As shown in FIG. 1, a P-NIL process is illustrated using a P-NIL resin 100 as disclosed herein. To perform the P-NIL process, the P-NIL resin 100 is dispensed or "coated" onto a substrate 102 via a coating device 104 as shown in FIG. 1a. The P-NIL resin 100 may include an optional solvent. If the P-NIL resin 100 includes a solvent, the solvent can be removed by applying heat 106 to the P-NIL resin 100 after coating onto the substrate 102 to evaporate the solvent as generally known in the art as shown in FIG. 1b. Then, as shown in FIGS. 1c-1d, a stamp 108, also referred to as a pattern, is pressed into the P-NIL resin 100. The stamp 108 can include nanometer features 110 embossed on the P-NIL resin 100. As shown in FIG. Id, the P-NIL resin 100 can be cured via photolysis 112 by using UV or visible light. Finally, the stamp 108 is removed as shown in FIG. 1, resulting in a hardened P-NIL resin 100 having the nanometer features 100 imprinted thereon.

[0020] In addition to being photochemically cured to provide a high refractive index film, the P-NIL resin 100 must meet several conditions, and viscosity control is crucial. For example, the viscosity of the formulation must be low enough to allow uniform, extremely thin films of 0.1-4 microns to be produced by spin coating. Achieving a low enough viscosity for extremely thin films is obtained by adding a solvent to the P-NIL resin 100. After removal of the solvent, the hybrid resin must remain sufficiently fluid so that it can fill the features of the stamp 108 (or mold) by capillary action preventing unnecessary wear or damage to the stamp. The P-NIL resin 100 can contain a solvent to give it a viscosity of <500 cps before heating in FIG. 1b. After removal of the solvent, the P-NIL resin 100 can have a viscosity of <4000 cps to allow it to fill the features in the mold or from the stamp 108 by capillary action. The P-NIL resin 100 can be imprinted to precisely capture the nanometer features 110, and the cured P-NIL resin 100 that forms a thin cured film on the substrate 102 has sufficient strength to maintain the nanometer features 110 when the stamp 108 is removed from the cured film and when the part or assembled device is heated in subsequent processing and / or operations.

[0021] In addition, the cured resin must be able to meet industrial level testing requirements, such as 1,000 hours at 85°C and 85% humidity without significant degradation. Finally, for optical applications as mentioned in the background, the refractive index of the cured resin must be >1.6 at 589nm, and for many AR / VR / MR applications, >1.7 at 589nm to achieve a wide field of view (FOV).

[0022] In one embodiment, the P-NIL resin 100 includes organic compounds or organic binders and inorganic nanoparticles mixed together in a prepolymerized liquid medium. The P-NIL resin 100 with both organic compounds and inorganic nanoparticles can be used at room temperature in P-NIL technology to maintain high RI values ​​and excellent mechanical properties such as glass transition temperature. The increased RI of the P-NIL resin 100 allows for device miniaturization in photonics and optical applications such as optical diffusers, wave guides, and optical elements for AR / VR / MR applications.

[0023] For the P-NIL resin 100 to be useful and practical in real life applications of AR / VR / MR and optical sensors, the P-NIL resin 100 must meet three requirements. Requirement 1: For the imprint process of thin-layer nanostructures (10-4000 nm), the P-NIL resin 100 must have good flowability. The viscosity of the organic binder must be 10-5,000 cps, and the viscosity of the P-NIL resin 100 must be 50-6,000 cps. Requirement 2: The P-NIL resin 100 must be mechanically tough and present high reliability for the use of optical devices. Requirement 3: The inorganic nanoparticles in the P-NIL resin 100 must have a particle size of <50 nm to achieve high light transmission, high transparency, and low haze.

[0024] The organic compound may be selected from the group consisting of acrylate-based resins, epoxy-based resins, brominated aromatic compounds, sulfur-containing compounds, or another organic compound having a RI value of greater than 1.5 at 589 nm.

[0025] The inorganic nanoparticles of the P-NIL resin 100 are nanometer-sized particles with high RI values. The inorganic nanoparticles can be selected from materials such as, but not limited to, silicon carbide (SiC), silicon nitride (Si3N4), zinc oxide (ZnO), zirconium oxide (zirconia, ZrO2) and titanium oxide (titania, TiO2). To avoid light scattering and maintain the transparency of the formulation, these particles should be less than 50 nm, or less than 30 nm, and should also have a high RI value of greater than 1.6 at 589 nm.

[0026] In addition, to avoid the inorganic nanoparticles from agglomerating with the organic compounds in the prepolymerized liquid medium, the inorganic nanoparticles can be functionalized or capped with an organic coating layer that can be uniformly dispersed or chemically bonded to the organic compounds of the P-NIL resin 100. As is generally known in the art, many types of high RI inorganic nanoparticles are available in small sizes and with organic coatings. For example, zirconium oxide and titanium oxide particles coated with organic layers in the size range of 10-20 nm are commercially available.

[0027] In addition to these two types of inorganic materials, other high RI inorganic materials are commercially available that do not contain an organic layer but are in the size range of 5-50 nm, which can be capped or coated with an organic layer using conventional functionalization chemistries as generally known in the art. Acceptable organic layers include, but are not limited to, silane capping agents, carboxylic acid capping agents, waxes, and amines.

[0028] In one embodiment, the P-NIL resin 100 is first formulated with a relatively high RI organic resin, such as an organic resin with a refractive index greater than 1.52 at 589 nm, that exhibits excellent mechanical performance characteristics. Inorganic nanoparticles with high RI are then added to form a hybrid organic / inorganic resin as the P-NIL resin 100. The cured P-NIL resin 100 then obtains a high RI while maintaining acceptable mechanical performance.

[0029] As shown in Fig. 1, P-NIL resin 100 can be used in P-NIL technology for use in diffractive optical elements (DOEs), including optical diffusers and waveguides that control the phase of transmitted light, and optical elements for AR / VR / MR devices. P-NIL resin 100 can be coated onto a substrate 102 made of glass, silicon, or the like, and then a stamp 108 or master template containing nanometer features 110 is pressed onto the P-NIL resin 100. The P-NIL resin 100 is then cured by UV or visible light, and then the stamp 108 is removed and the nanometer features 100 are embossed onto the cured P-NIL resin 100, which has high RI and acceptable mechanical properties.

[0030] As mentioned above, simply obtaining a high RI in a material does not necessarily make it suitable for P-NIL applications. The physical mechanical and toughness properties of the high RI material must be controlled by design. For example, a high RI P-NIL / 2P resin should have high transparency in the visible spectrum, resulting from the lack of absorbance, and low haze from light scattering. The P-NIL resin 100 must also exhibit limited shrinkage during the curing process. The cured P-NIL resin 100 must adhere to the surface of a tough material, such as glass or silicon wafer, and pull away from the surface of a mold or working stamp 108. The cured P-NIL resin 100 must be strong enough not to tear when handled, and rigid enough so that the nanometer features 110 from the stamp 108 do not deform. What is important is that the glass transition temperature (Tg) of the cured P-NIL resin 100 should be high enough so that deformation and excessive thermal expansion do not occur under normal operating conditions.

[0031] To achieve the desired properties, photocurable acrylate or photocurable epoxy can be used as a component of the organic binder. Details of photocurable acrylate organic binder and photocurable epoxy organic binder are described below.

[0032] Light-curable acrylate organic binders: Four "acrylate components" can be used to design a photocurable acrylate (or methacrylate) organic binder that meets the required properties. The first acrylate component should be one or more low viscosity monomers that can be used as a diluent for viscosity adjustment. Aliphatic or aromatic monomers can be used as viscosity dilution aids, but aromatic monomers are preferred to ensure a high refractive index organic binder. The second acrylate component should be a multifunctional acrylate or methacrylate monomer or oligomer to provide high crosslink density and high Tg in the final cured film. The third acrylate component should be one or more adhesion promoters that are used to ensure good adhesion and high reliability of the final cured film. The fourth acrylate component should be one or more photoinitiators with activation wavelength in the range of 300-500 nm.

[0033] First Acrylate Component: It is desirable to use mono-, di- or tri-acrylates which have low viscosity. Specific examples of mono- or di-acrylate monomers include, but are not limited to, the following: neopentyl diacrylate, isobornyl acrylate, diacrylate of hydroxypivalaldehyde modified trimethylolpropane, neopentyl hydroxypivalate glycol diacrylate, diacrylate of tricyclodecane dimethanol, cyclohexane dimethanol dimethacrylate, ethoxylated bisphenol A diacrylate, tripropylene glycol diacrylate, triethylene glycol diacrylate, 1,3-butylene glycol dimethacrylate, dimethacrylate of ethylene oxide modified bisphenol A, t-butyl methacrylate, PEG#200 diacrylate, 3-methyl-1,5-pentanediol diacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, 2-methyl-1,8-octanediol diacrylate, 1,9-nonanediol diacrylate, or the like. To arrive at an organic binder with a high refractive index, it is desirable to use high refractive index monomers, thereby keeping the amount of high refractive index inorganic particles to a minimum, which achieves high fluidity. Desirable monomers have a homopolymer film refractive index in the range of 1.51 to 1.58 at 589 nm. Examples of these types of high refractive index monomers are listed in Table 1.

[0034] [Table 1]

[0035] Second Acrylate Component: To achieve a glass transition temperature of the cured film of >50°C, multifunctional acrylate or methacrylate monomers or oligomers are used. This results in high crosslink density and Tg>50°C of the cured film. Examples of multifunctional acrylates include, but are not limited to, trimethylolpropane tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, di(trimethylolpropane)tetraacrylate, dipentaerythritol pentaacrylate, trimethylolpropane triacrylate, or the like. The multifunctional acrylate monomer or oligomer can be selected from high refractive index type resins, including, but not limited to, bisphenol A epoxy di-tri-acrylate, 9,9-bis[4-(2-acryloyloxyalkoxy)phenyl]fluorene-di-acrylate. Typically, multifunctional acrylates have a high viscosity, and the proportion of multifunctional acrylate used in the PNIL-R composition must be optimized to achieve suitable fluidity for the imprint process.

[0036] Third Acrylate Component: Adhesion promoters are used as chelating agents to obtain strong adhesion to the base substrate and to provide high reliability performance to the patterned cured P-NIL resin. The following types of chelating agents have been found to be effective: carboxylic acid type acids, phosphoric acid type acids, metal hybrid acrylates, silane coupling agents, basic type adhesion promoters containing amines or amide type adhesion promoters containing amine-based acrylates. Specific examples of chelating agents include, but are not limited to, the following: amine acrylates including CN373, CN984, CN384, CN386, and CN371, SR368 manufactured by Arkema Sartomer, dimethylaminoethyl methacrylate manufactured by Kyoeisha Chemical Co., Ltd.; acid-based chelating agents such as phosphate of caprolactone-modified 2-hydroxyethyl methacrylate manufactured by Nippon Kayaku Co., Ltd., 2-hydroxyethyl methacrylate phosphate manufactured by Kyoeisha Chemical Co., Ltd., 2-methacryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl succinic acid, 2-methacryloyloxyethyl hexahydrophthalate, 2-acryloyloxyethyl succinate, 2-acryloyloxyethyl phthalate, 2-acryloyloxyethyl phosphate, 2-acryloyloxyethyl phosphate diacrylate, 2-acryloyloxyethyl hexahydrophthalate manufactured by OSI Chemical Co., Ltd. Silane chelating agents include γ-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane manufactured by Specialties.

[0037] Fourth Acrylate Component: Both short and long wavelength radical-induced photoinitiators can be used. The choice of short or long wavelength radical-induced photoinitiator is based on the UV light source used in the NIL process. Examples of short wavelength radical-induced photoinitiators include, but are not limited to, benzophenone, 2-hydroxy-2-methyl-l-phenylpropan-l-one (BASF Irgacure 1173), 1-hydroxycyclohexylphenyl-ketone (BASF Irgacure 184). Long wavelength radical-induced photoinitiators include, but are not limited to, diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide (BASF Darocure TPO), phosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)-phosphine oxide (BASF Irgacure 819), l,2-diphenyl-2,2-dimethoxyethanone (BASF Irgacure 651).

[0038] Examples of photocurable acrylate organic binders are listed below.

[0039] Photocurable acrylate example 1:

[0040] [Table 2]

[0041] Photocurable acrylate example 2:

[0042] [Table 3]

[0043] Photocurable acrylate example 3:

[0044] [Table 4]

[0045] Light-curable epoxy organic binder: Photocurable epoxy organic binders contain three "epoxy" components: component 1: a polymerizable epoxide or oxetane; component 2: a silane coupling agent; and component 3: a photo-acid-generator (PAG).

[0046] Epoxy Component 1: Polymerizable epoxides or oxetanes are commercially available or can be synthetically prepared. Non-limiting examples of suitable commercially available epoxide compounds include 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, diglycidyl ester of hexahydrophthalic acid, 2,2-bis[4-(glycidyloxy)phenyl]propane, bisphenol A diglycidyl ether, and bisphenol F diglycidyl ether, among others.

[0047] Epoxy Component 2: Since photocurable epoxy binders are polymerized using a cationic pathway, the silane coupling agent must not be basic in nature. The most preferred silane coupling agent is an epoxy-functional silane. Examples of epoxy-functional silanes include, but are not limited to, 3-glycidoxypropylmethyldimethoxysilane (KBM-402, Shin-Etsu Chemical Co., Ltd.), 3-glycidoxypropyltrimethoxysilane (KBM-403, Shin-Etsu Chemical Co., Ltd.), 3-glycidoxypropylmethyldiethoxysilane (KBE-402, Shin-Etsu Chemical Co., Ltd.), and 3-glycidoxypropyltriethoxysilane (KBE-403, Shin-Etsu Chemical Co., Ltd.).

[0048] Epoxy Component 3: Photoacid Generators (PAGs) induce acid-catalyzed polymerization of polymerizable epoxides / oxetanes by forming a superacid when exposed to UV or visible light. Suitable PAGs can be selected from known photochemically active "onium" salts (e.g., sulfonium, iodonium, etc.) and neutral compounds (e.g., sulfonate esters) that react in the presence of UV light to produce a superacid that induces acid-catalyzed polymerization of polymerizable epoxides / oxetanes. As will be understood by those skilled in the art, a superacid is an acid that has an acidity greater than that of 100% sulfuric acid. For example, the PAG can be a sulfonium salt with a counterion that protonates to form a superacid when exposed to UV light. Alternatively, the PAG can be a sulfonate ester that hydrolyzes to form a superacid when exposed to UV light. In particular, superacids generated by PAGs may contain conjugate bases that do not fully bind protons, such as hexafluorophosphate, hexafluoroantimonate, sulfonate, and tetrakis(pentafluorophenyl)borate, among others.Of particular interest in this regard are commercially available PAGs that react in the presence of 365 nm light, including diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate, a mixture of diphenyl[4-(phenylthio)phenyl]sulfonium bis(heptafluoropropyl)tetrafluorophosphate and diphenyl[4-(phenylthio)phenyl]sulfonium tris(heptafluoropropyl)trifluorophosphate, and diphenyl[4-(phenylthio)phenyl]sulfonium hexafluoroantimonate and bis(4-diphenylthio)phenyl]sulfonium tris(heptafluoropropyl)trifluorophosphate. mixture of diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate and bis(4-diphenylthiophenyl)sulfide bis(hexafluorophosphate), tris[4-(4-acetylphenylthio)phenyl]sulfonium tetrakis(pentafluorophenyl)borate, tris[4-(4-acetylphenylthio)phenyl]sulfonium tris(trifluoromethylsulfonyl)methide, and (2-methylphenyl)-2-[[[(4-methylphenyl)sulfonyl]oxy]imino]-thiopheneacetonitrile.

[0049] Examples of photocurable epoxy binders are listed below.

[0050] Light-curing epoxy example 1:

[0051] [Table 5]

[0052] Light-curing epoxy example 2:

[0053] [Table 6]

[0054] Light-curing epoxy example 3

[0055] [Table 7]

[0056] To assemble the photo-nanoimprint lithography resin composition, a dispersion of high refractive index inorganic nanoparticles <50 nm in size is used. Inorganic dispersions of high refractive index nanoparticles, including but not limited to ZrO2 and TiO2, in organic solvents (such as l-methoxy-2-propanol, propylene glycol methyl ether acetate, isopropyl alcohol, ethyl acetate, or n-butyl acetate or the like).

[0057] Commercially available ZrO2, TiO2 dispersions or the like can be obtained from Pixelligent Technologies LLC (USA), Teika Corporation (Japan), or Osaka Gas Chemicals Co., Ltd. (Japan). TiO2 has a higher refractive index than ZrO2, so TiO2 is used to achieve the optimum high refractive index, but any type of inorganic dispersion compatible with the low viscosity high Tg photo-reactive organic binder can be utilized. To achieve RI values ​​of 1.6-2.0 at 589 nm, the inorganic dispersion is used in the range of 5-95% by volume, and the low viscosity high Tg organic binder is used in the range of 5-85% by volume. To achieve RI values ​​above 1.6, blends or mixtures of different inorganic nanoparticles can also be utilized, such as a 50% ZrO2 / 50% TiO2 blend of inorganic nanoparticles, or a 75% ZrO2 / 25% TiO2 blend.

[0058] The optical performance of each P-NIL resin 100 was characterized by the following method: P-NIL resin 100 was coated onto 120 μm borosilicate glass and soft baked at 100° C. for 60 seconds with 30 J / cm 2The films were cured with 365 nm LED light or UV-A light. Refractive index and film thickness were measured with a Metricon Model 2010M prism coupler at 25° C. and wavelengths of 457, 516, 638, and 854 nm, and the data was resolved as Cauchy functions. Percent transmission, haze, and clarity were measured using a BYK Haze-Guard i instrument for thin films coated on glass.

[0059] In one embodiment of the P-NIL resin 100 formulation, an acrylate-based resin with RI=1.60 at 589 nm was combined with coated 20 nm TiO2 particles to give a RI=1.76 at 25° C. and 589 nm. The formulation contained 40% by weight of the acrylate-based resin and 60% by weight of the TiO2 particles. The Tg of this material was 63° C.

[0060] In another embodiment, the formulation was changed to 20 wt% acrylate resin and 80 wt% TiO2 particles, resulting in a cured formulation with RI=1.82 at 589 nm and 25° C. The Tg of this formulation was 69° C.

[0061] Further examples of P-NIL resins 100 and their optical performance are listed below.

[0062] PNIL-R Example 1:

[0063] [Table 8]

[0064] PNIL-R Example 2:

[0065] [Table 9]

[0066] PNIL-R Example 3:

[0067] [Table 10]

[0068] PNIL-R Example 4:

[0069] [Table 11]

[0070] The reliability performance of PNIL-R was studied as follows: Cured films of P-NIL coated on borosilicate glass were placed in an environmental stress chamber at 85° C. and 85% relative humidity. The coated samples were open to the atmosphere. After 1,100 hours, the coated samples were analyzed for percent transmission, haze, and clarity. Excellent optical properties were retained after 1,100 hours at 85° C. and 85% relative humidity.

[0071] Example reliability performance results are summarized below.

[0072] PNIL-R Example 1:

[0073] [Table 12]

[0074] PNIL-R Example 2:

[0075] [Table 13] [Explanation of symbols]

[0076] 100P-NIL resin 102 Substrate 104 Coating device 106 fever 108 Stamps 110 nanometer feature 112 Photolysis using UV or visible light

Claims

1. A photo-nanoimprint lithography (P-NIL) resin, Crosslinkable organic binders; a solvent-based inorganic nanoparticle dispersed in the P-NIL resin; and a solvent configured to evaporate; the P-NIL resin has a viscosity in the range of 4,000 to 6,000 centipoise at 25° C. after evaporation of the solvent prior to curing the P-NIL resin; The P-NIL resin has a refractive index greater than 1.6 at 589 nm and a glass transition temperature greater than 50° C. after being cured with a photoinitiator. P-NIL resin.

2. 10. The P-NIL resin of claim 1, wherein the crosslinkable organic binder reacts by photochemically induced radical polymerization or photochemically induced acid catalyzed polymerization.

3. 3. The P-NIL resin of claim 2, wherein the photocurable organic binder has a viscosity in the range of 2,000 to 5,000 cps at 25°C.

4. 3. The P-NIL resin of claim 2, wherein the organic binder is photocurable upon polymerization to provide a solid having a glass transition temperature greater than 50°C.

5. 3. The P-NIL resin of claim 2, wherein the solvent-dispersed inorganic particles have a particle size of less than 50 nm.

6. 3. The P-NIL resin of claim 2, wherein the volume of inorganic particles is in the range of 5 to 95 volume percent.

7. 3. The P-NIL resin of claim 2, wherein the photocurable organic binder is in the range of 5 to 85 volume percent.

8. 3. The P-NIL resin of claim 2, used for the production of nano-patterning by using photo-, UV-, light-activated nanoimprint lithography manufacturing processes.

9. 9. The P-NIL resin of claim 8, wherein the nanoimprinted layer has a thickness in the range of 10 to 10,000 nm.

10. 9. The P-NIL resin of claim 8, wherein the P-NIL resin applied to a working stamp is light-transmitting for photocuring, and the working stamp is selected from the group consisting of polydimethylsilicone (PDMS), quartz, metal, and polymer.

11. 9. The P-NIL resin of claim 8, wherein the P-NIL resin applied onto a substrate is light-transmitting for photocuring, and the working stamp is selected from the group consisting of polydimethylsilicone (PDMS), quartz, metal, and polymer.

12. 10. The P-NIL resin of claim 1, wherein the crosslinkable organic binder reacts by photochemically induced radical polymerization, and the photocurable organic binder comprises a monomer or oligomer having acrylate or methacrylate repeat units.

13. 10. The P-NIL resin of claim 1, wherein the crosslinkable organic binder reacts by photochemically induced acid catalyzed polymerization, and the photocurable organic binder comprises a monomer or oligomer having epoxy or oxetane repeat units.

14. A photopolymer (2P) resin for use in photonic nanoimprint lithography for photonics and optics applications, comprising: organic compounds; Contains inorganic nanoparticles less than 50 nanometers in size; The organic compound has a minimum refractive index value of 1.5 and is selected from the group consisting of acrylate-based resins, epoxy-based resins, materials containing brominated aromatic compounds, and sulfur-containing compounds; said inorganic nanoparticles having a minimum refractive index value of 1.6 at 589 nm and selected from the group consisting of silicon carbide, silicon nitride, zinc oxide, zirconium oxide, titanium oxide, and mixtures thereof; said organic compound and said inorganic nanoparticles are combined in a prepolymerized liquid medium; The cured product obtained after the curing process has a refractive index of 1.65 or more at 589 nm and a glass transition temperature of 50° C. or more. Photopolymer (2P) resin.

15. 3. The 2P resin of claim 2, wherein the photocurable organic binder has a viscosity in the range of 2,000 to 5,000 cps at 25°C.

16. 16. The 2P resin of claim 15, wherein the organic compound polymerizes to give a solid having a glass transition temperature greater than 50°C.

17. 16. The 2P resin of claim 15, wherein the volume of the inorganic nanoparticles is in the range of 5 to 95% by volume.

18. 16. The 2P resin of claim 15, wherein the organic compound is in the range of 5 to 85% by volume.

19. 1. A method for producing a photo-nanoimprint lithography (P-NIL) resin, comprising: providing an uncured P-NIL resin comprising a crosslinkable organic binder, solvent-based inorganic nanoparticles dispersed in the uncured P-NIL resin, and a solvent having a viscosity in the range of 4,000 to 6,000 centipoise at 25°C; coating the uncured P-NIL resin onto a substrate; applying heat to the uncured P-NIL resin to evaporate the solvent; imprinting the uncured P-NIL resin with a stamp having nanometer-sized features; curing the uncured P-NIL resin with a photoinitiator; removing the stamp; wherein the resulting P-NIL resin has a refractive index greater than 1.6 at 589 nm, a glass transition temperature greater than 50° C., and said nanometer-sized features.

20. providing a solvent-free uncured P-NIL resin; imprinting the uncured P-NIL resin with a stamp having nanometer-sized features; curing the uncured P-NIL resin with a photoinitiator; removing the stamp; 20. The method of claim 19, further comprising:

Citation Information

Patent Citations

  • Photocurable composition and pattern forming method

    US20220334475A1